I need to solve this equation: Log(3x+5) = 1 + (log (x-1)

log(3x + 5) = 1 + log(x - 1)

log(3x+5) - log(x-1) = 1

log[(3x+5)/(x-1)] = log10

(3x+5)/(x-1) = 10 **(x≠1)**

3x + 5 = 10(x - 1)

3x - 10x = -5 - 10

-7x = -15 --->** x = 15/7**

I need to solve this equation: Log(3x+5) = 1 + (log (x-1)

Tutors, please sign in to answer this question.

log(3x+5) - log(x-1) = 1

log[(3x+5)/(x-1)] = log10

(3x+5)/(x-1) = 10 **(x≠1)**

3x + 5 = 10(x - 1)

3x - 10x = -5 - 10

-7x = -15 --->** x = 15/7**

woops, my bad x = 15/7

I think there is an error here. Since the bases are the same when you move the log(x-1) to the left, we could use the quotient rule of logs to get Log(3x+5)/(x-1)=1...which we can rewrite in exponential form; 10^1=(3x+5)/(x-1)...which gives us 10x-10=3x+5....7x=15....x=15/7

Hi Thomas. There is no any evidence, that given logarithm is natural (ln).

## Comments